Comprehensive genetic characterization of CLL: a study on 506 cases analysed with chromosome banding analysis, interphase FISH, IgV(H) status and immunophenotyping - Haferlach, C; Dicker, F; Schnittger, S; Kern, W; Haferlach, T (Leukemia, 2007)
In CLL data from chromosome banding analysis (CBA) have been scarce due to the low proliferative activity of CLL cells in vitro. We improved the cultivation technique using an immunostimulatory CpG-oligonucleotide DSP30 and IL-2. A total of 506 CLL samples were analysed with CBA and interphase FISH using probes for the detection of trisomy 12, IgH rearrangements and deletions of 6q21, 11q22.3 (ATM), 13q14 (D13S25 and D13S319) and 17p13 (TP53). A total of 500 of 506 (98.8%) cases were successfully stimulated for metaphase generation and are subject to this study. Aberrations were detected in 415 of 500 (83.0%) cases by CBA and in 392 of 500 (78.4%) cases by FISH. CBA detected 832 abnormalities and FISH only 502. Therefore, CBA offers important information in addition to FISH. (1) CLL is characterized mainly by genomic imbalances and reciprocal translocations are rare. (2) A subgroup with complex aberrant karyotype (16.4%) is identified which is associated with an unmutated IgV(H) status and CD38 expression (P=0.034 and 0.02, respectively). (3) Additional abnormalities are detectable providing new biological insights into different CLL subclasses revealing a much more heterogeneous pattern of cytogenetic abnormalities as assumed so far based on FISH data only. Therefore, prospective clinical trials should evaluate the prognostic impact of newly available CBA data.